Recurrent Kaposi sarcoma associated with Koebner phenomenon in two HIV-seronegative patients: Two case reports and a review of the literature. Issue 52 (December 2017) - Marino, Dario; Calabrese, Fiorella; Ottaviano, Giancarlo; La Torre, Fabio Biagio; Vicario, Mattia; Alaibac, Mauro; Calabrò, Maria Luisa
Abstract: Rationale: Koebner phenomenon is occasionally reported in patients affected by classic Kaposi sarcoma (KS). Patient concerns: Here, we report 2 cases of KS associated with Koebner phenomenon and the correlation of human herpesvirus 8 molecular analysis with the clinical outcome. Interventions: In the first case, a patient with a history of sporadic cutaneous KS developed a recurrent lesion at the laryngeal tract, the site of a previous nodulectomy. In our second case, immunodeficiency induced by chemotherapy triggered the development of KS and Koebner phenomenon was limited to the skin at the site of safenectomy. Lessons: Our observations suggest that careful planning of surgical treatment is required in immunocompetent and immunocompromised patients with a medical history of KS. Moreover, mucosal sites (both respiratory and in the gastrointestinal tract) should be considered as potential sites for KS development.